Sistem Inventory Menggunakan Metode Supply Chain Management dalam Mengatur Jumlah Ketersediaan Obat pada Apotik - Pratiwi, Mutiana; Ilhami Arsyah, Ulya; Pramana Gusman, Aggy; Muhammad, Abulwafa (Institut Riset dan Publikasi Indonesia, 2021)
The development of information technology provides great benefits and convenience, both in terms of data processing and presentation of information on inventory of existing goods in organizations, agencies or companies. One of the business processes that can be developed through information technology is the company's supply chain management process. An inventory information system using a good Supply Chain Management (SCM) method will increase the productivity and performance of the company. In conducting the research conducted at the pharmacy, the aim was to improve the old system. By conducting direct observations in the field, several weaknesses were found from the system that was running at the Arafah Padang Pharmacy. The results of the analysis are applied in an application that is able to process inventory system data using the Supply Chain Management (SCM) method. With the design of an inventory system with the Supply Chain Management (SCM) method, it can be more helpful in processing drug inventory data and the existing inventory system can increase the effectiveness and work efficiency of Pharmacy employees.